(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
The article focuses on the new reforms carried out in the framework of the state policy on the issue of treatment of women in New Uzbekistan and their legal framework, protection of women’s rights, freedoms and legitimate interests, increasing the social activity of women today, increasing their position in the family and society and the issues of increasing the role of women’s labor in the development of small business and private entrepreneurship, the role of women entrepreneurs in the modern world, support for women’s entrepreneurship and the creation of a business environment.